الحقيقة الوضعية اللغوية وأثرها في فهم النص القرآني = The linguistic basic pillar in understanding the texts of the Holy Qur’an = Tunjang asas linguistik dalam memahami teks-teks Al-Quran - Abdo Khaled, Nashwan; Tahhan, Mohammed Abdulraheem A M (IIUM Press, 2023)
يهدف هذا البحث إلى بيان ركن أساسي في فهم نصوص القرآن الكريم وهو الحقيقية اللغوية، فمن المعلوم بيقين أن لهذا النوع من الوحي (القرآن الكريم) اصطلاحاً خاصاً لا يعرف إلا به ومن قِبله. فالضوابط التي يفهم من خلالها النص القرآني ثلاث حقائق: حقيقة وضعية وهي نوعان: وضعية لغوية أصلية، ووضعية لغوية فرعية، وحقيقة شرعية دينية، وحقيقة عرفية اصطلاحية. وهذه الدراسة تتناول الحقيقة الوضعية اللغوية، لتوضيحها وبيان طريقة الفهم من خلال تلك الحقيقة، ومعرفة المقبول من المردود مما ينسب للنص القرآني الكريم من معاني، فهي أي الحقيقة اللغوية الأسبق وجوداً والقرآن الكريم نزل باللغة العربية الفصحى. وسيكون ذلك من خلال استقراء وتحليل نصوص القرآن الكريم التي تؤكد ذلك المعنى. وانتهت الدراسة إلى أنه لا بد في فهم النصوص القرآنية من اتباع معهود العرب الذين نزل القرآن بلسانهم فإن كان للعرب في لغتهم عرف مستمر، فلا يصح العدول عنه في فهم النصوص القرآنية. وهذا جار في المعاني والألفاظ والأساليب، وعليه فلا يستقيم للمتكلم في كتاب الله تعالى أن يتكلف فوق ما يسعه لسان العرب. ***** This research aims to explain a basic pillar in understanding the texts of the Holy Qur’an, which is the linguistic dimension. It is known with certainty that this type of revelation (the Holy Qur’an) has a special term that is known only by it and by it. The controls through which the Qur’anic text is understood are three facts: a positive truth, which has two types: an original linguistic position, a sub-linguistic position, a religious legal fact, and a conventional customary fact. This study deals with the positive linguistic truth, to clarify it and explain the method of understanding through that truth, and to know which meaning attributed to the Holy Qur’anic text is acceptable and which is rejected. It is the linguistic dimension that was the first to exist and the Holy Qur’an was revealed in classical Arabic, and this will be through extrapolation and analysis of the texts of the Holy Qur’an. The study concluded that in understanding the Qur’anic texts it is necessary to follow the custom of the Arabs in whose language the Holy Qur’an was revealed. If the Arabs have a continuous custom in their language, it is not permissible to deviate from it in understanding the Qur’anic texts, and this applies to meanings, wording and methods. Therefore, it is not necessary for anyone who wants to talk about the book of God to invent meanings that do not exist in the scope of the Arabic language. ***** Kajian ini bertujuan menjelaskan satu elemen asas dalam memahami teks-teks al-Quran iaitu aspek linguistik. Seperti yang diketahui dengan pasti bahawa wahyu jenis ini (Al-Quran) hanya boleh difahami melalui istilahnya yang khusus. Teks al-Quran boleh difahami melalui tiga eleman utama: elemen waḍ’ī (perletakan makna). Elemen ini mempunyai dua jenis: Pertama perletakan makna asal, dan perletakan makna cabang, manakala elemen kedua adalah syariat atau agama, dan elemen ketiga iaitu adat. Kajian ini berkaitan dengan elemen bahasa. Kajian bertujuan menjelaskan makna kaedah pemahaman melalui elemen bahasa. Selain itu, ia juga bertujuan menyingkap makna-makna yang boleh diterima dan tertolak dalam berinteraksi dengan teks Al-Quran. Ini kerana elemen bahasa adalah eleman yang paling awal wujud. Al-Quran diturunkan dalam bahasa Arab klasik. Kajian akan meneliti dan menganalisis teks-teks Al-Quran yang mengesahkan makna itu. Dapatan kajian merumuskan bahawa dalam memahami nas-nas al-Quran perlu mengikut adat bahasa orang Arab kerana Al-Quran diturunkan dengan bahasa mereka. Jika orang Arab mempunyai adat yang lestari dalam bahasa mereka, kita tidak dibenarkan menyimpang daripada adat tersebut dalam memahami teks-teks Al-Quran. Hal ini terpakai kepada makna, perkataan dan kaedah. Oleh itu, tidak harus bagi sesiapa yang ingin berbicara tentang kitab Allah untuk mengada-adakan makna yang tidak ada dalam ruang lingkup bahasa Arab.